Detailed characterisation of TiO2 nano-aggregate morphology using TEM image analysis. (July 2019) - Manuputty, Manoel Y.; Lindberg, Casper S.; Botero, Maria L.; Akroyd, Jethro; Kraft, Markus
Abstract: A detailed morphological characterisation is performed on flame synthesised TiO 2 nano-aggregates (number of primaries, N < 10 ) using transmission electron microscopy (TEM) image analysis and mobility measurements. The size-dependent collection efficiency of the TEM sampling method is accounted for with a simple correction for particle deposition through impaction and diffusion. The TEM-derived sizes show excellent agreement with electrical mobility measurements. Primary particle size, aggregate size, and degree of aggregation distributions were obtained for two different flames and varying precursor loading rates. The analysis reveals some particle aggregation which is likely to occur only very late in the growth stage, leading to the similarity between the primary particle and spherical particle size distributions. The degree of aggregation is defined as the ratio of gyration to spherical equivalent sizes from the projected area analysis, allowing identification of particles with spherical and non-spherical morphologies. The size distributions are found to be strongly affected by precursor loading but not by flame mixture or maximum temperature. In all cases, approximately 60–70% particles are spherical while the rest form small aggregates. The detailed morphological information reported provides the much-needed experimental data for studying the early stage particle formation of TiO 2 from titanium tetraisopropoxide (TTIP) in a well-defined burner configuration. Highlights: A TEM sampling method is presented which relies on impaction and diffusion mechanisms for particle deposition. A semi-automated image analysis algorithm is employed for aggregate morphological characterisation. A measure of particle aggregation using the ratio of gyration to spherical equivalent sizes is proposed. Primary particle size, aggregate size, and degree of aggregation distributions are reported.